Optimización de costos de inventarios con algoritmo de programación lineal. Caso aplicado industria de producción de suelas - Aldás Salazar, Darwin (2018)
In this research it has been proposed a mathematical algorithm of lineal programming that evaluates the conditions that intervene in the inventories of raw materials stored in a shoe soles industry such as the demand, the limit of the productive capacity, and the related costs of carrying inventory; it is generated an objective function and its respective restrictions of the system, the same that is modeled and solved in a Lingo® programming software, the algorithm enables the optimization of the amounts of material to be required, inventory at the end of each period and the amount of missing units with the finality of satisfying the demand and both minimizing the total cost of the inventory maximizing the profit in planning ́s horizonof twelve months. As a result, the mathematical model presented to the control of raw material inventory that generates saving money per year of $ 52566.50, which come to an improvement of 25.6% with respect to the current model.